Digital Content Quality and Brand Engagement: Evidence from SKIN1004's TikTok Followers in Indonesia - Yabes Edmund Macario Siburian; Menati Fajar Rizki (Golden Ratio of Mapping Idea and Literature Format, 2026)
Despite reaching more than 724,000 followers, the official TikTok account of SKIN1004 Indonesia (@skin1004_indonesia) shows a persistent gap between video views and audience interaction, with some uploads generating engagement rates below 0.1 percent. This gap raises the empirical question of whether digital communication content quality explains the low level of follower engagement, a relationship that remains underexamined for South Korean skincare brands operating in the Indonesian TikTok market. This study aims to examine the influence of SKIN1004's digital communication content quality on brand engagement among the followers of its TikTok account. A quantitative explanatory survey method was employed, with a sample of 100 respondents selected through purposive sampling and the Slovin formula (10 percent margin of error) from a population of 724,668 followers. Content quality was measured across five dimensions (relevance, originality, interaction, consistency, and emotionality), while brand engagement was measured across three dimensions (cognitive, emotional, and behavioral). Simple linear regression showed that content quality significantly and positively predicted brand engagement (Y = 5.421 + 0.517X; t = 15.720 > t-table 1.984; p < .001), with a very strong correlation (r = 0.846) and 71.6 percent explained variance (R² = 0.716). Originality emerged as the weakest content dimension, while behavioral engagement was the weakest engagement dimension, pointing to specific, actionable priorities for skincare brands seeking to convert passive viewership into deeper follower engagement on TikTok.